Illness Narrative, Depression, and Sainthood An Analysis of the Writings of Mother Teresa - Williams, S. Taylor (2014)
In 2007, the letters of The Blessed Mother Teresa to her confessors were published for the public in a book entitled Come Be My Light. What surprised many readers was that Mother Teresa felt very distant from God and described feeling great "darkness" for many years. This paper draws parallels between the writings of Mother Teresa and those of writers' illness narratives describing the psychiatric condition of Depression. The author provides this textual analysis to explore Mother Teresa's experience within a psychiatric paradigm (Major Depressive Disorder), in comparison with and contrast to the spiritual paradigm of a "Dark Night of the Soul."
Keywords: Depression; Illness narrative; Literary Analysis; Mother Teresa